Liquid-crystalline coumarin derivatives: contribution to the tailoring of metal-free sensitizers for solar cells. Issue 2 (26th January 2018) - Merlo, Aloir A.; Tavares, Aline; Khan, Sherdil; Leite Santos, Marcos J.; Teixeira, Sergio Ribeiro
ABSTRACT: Coumarins have been used in a wide range of applications, such as dye-sensitised solar cells, laser dyes and optical sensors. In order to further explore the properties of these materials, three new coumarin derivatives were obtained with different terminal arylalkyne linkages to the 6-position of the coumarin core. The synthesised materials were characterised by NMR, absorption and emission spectroscopy, and the liquid crystal properties were investigated through differential scanning calorimetry and polarised optical microscopy. In addition, dye-sensitised solar cells were assembled to evaluate the photoelectrochemical properties of the materials. Only the coumarin with a naphthyl group exhibited stable smectic A and nematic mesophases. All the coumarins were photoemissive in the range 420–461 nm. The adsorption of these dyes on TiO2 was observed by UV–vis spectroscopy; in addition, by incident photon-to-electron conversion efficiency and I – V curves, photocurrent generation was observed. GRAPHICAL ABSTRACT: